Recent advances in PVP-assisted thermal treatment: Impact on nanostructure properties, potential applications, challenges, and future perspectives - Muhammad Noorazlan Bin Abd Azis (Tanjung Malim, 2024)
Recent advances in PVP-assisted thermal treatment: Impact on nanostructure properties, potential applications, challenges, and future perspectives by Muhammad Noorazlan Bin Abd Azis